INFLUENCE OF FOLIC ACID ON THE RATE OF CUMENE AUTOOXIDATION IN EMULSION (Proceedings of the YSU B: Chemical and Biological Sciences, 2011)
The influence of folic acid (FA) on the rate (R) of cumene autooxidation at 353 K and initiated by AIBN in H20/C6H5Cl emulsion stabilized by anionic surfactant sodium dodecylsulfate has been studied. It is established that in the presence of FA the reaction begins after some induction period (τ). The function τ = f ([FA]0 ) is being described by a bell-shape curve. At low FA concentrations prevails its inhibitory action. Increasing [FA]0 begins its cooxidation parallelly with cumene. FA practically does not act on the steady-state R. But in its presence after some time the steady-state trend of the reaction is being disturbed. The reaction is being continued with decreased rate. In the steady-state R ~ [AIBN ]$_0^{1/2}$ [cumene]0 . It is assumed that the products of FA transformation is not indifferent with respect to the kinetics of cumene autooxidation. Dianion, which corresponds to FA in a more extent decreases the reaction rate.
Keywords: folic acid; cumene; transformation; reaction rate